2015
DOI: 10.1287/isre.2015.0602
|View full text |Cite
|
Sign up to set email alerts
|

Embarrassing Exposures in Online Social Networks: An Integrated Perspective of Privacy Invasion and Relationship Bonding

Abstract: O nline social networks greatly facilitate social exchange among friends. At times, for amusement, individuals may be targeted by friends' playful teases, which often involve exposing individuals' private embarrassing information, such as information that reveals their past indecent behavior, mischief, or clumsiness. Although individuals sometimes do enjoy the humor, they might also be offended by the involuntary exposure. Drawing on social exchange theory, this paper elucidates the consequences of an embarras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 80 publications
(91 reference statements)
1
84
0
1
Order By: Relevance
“…It thus becomes incumbent on emergency responders to release reliable information, whilst trying to control collective anxiety in the community, to suppress the rumour threads . Furthermore, security concerns are increasingly common with involuntary online exposure on social media, and research on this subject suggests that information dissemination with network commonality affects privacy invasion and user bonding (Choi et al 2015). It has been learnt that an individual's or firm's decision to withhold information in the interest of privacy can have both positive and negative effects on their utility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thus becomes incumbent on emergency responders to release reliable information, whilst trying to control collective anxiety in the community, to suppress the rumour threads . Furthermore, security concerns are increasingly common with involuntary online exposure on social media, and research on this subject suggests that information dissemination with network commonality affects privacy invasion and user bonding (Choi et al 2015). It has been learnt that an individual's or firm's decision to withhold information in the interest of privacy can have both positive and negative effects on their utility .…”
Section: Discussionmentioning
confidence: 99%
“…Burtch et al (2016) analyse a large online crowd funding platform and report that when campaign contributors control/conceal visibility from public display, there is a negative impact on subsequent visitor's conversion likelihood and average contributions. In a different study, Choi et al (2015) find that information dissemination and network commonality has a high impact on individual's perception of privacy invasion and relationship bonding that impedes transactional and interpersonal avoidances.…”
Section: Risks and Concerns With The Use Of Social Mediamentioning
confidence: 94%
“…This introduces the problem known as interdependent privacy: users are no longer in control of their privacy as other users' actions and interactions can affect their privacy (Biczók and Chia 2013). Several research papers have enriched our understanding of interdependent privacy (Biczók and Chia 2013;Choi et al 2015;Pu and Grossklags 2015). However, very few papers focused on interdependent privacy in the OSNs domain.…”
Section: Interpersonal Privacy Concerns On Osnsmentioning
confidence: 99%
“…Even though no new information has been revealed, but aggregating interpersonal information can reveal more details about individuals in unexpected ways (Shi et al 2013). Choi et al (2015) offered insights on the effects of interdependent privacy by evaluating embarrassing exposures and found that even though users might feel embarrassed, they still value the social rewards of such disclosures. Although this stream of research has conceptually identified users' concerns towards interdependent privacy, there is a lack of research examining the extent to which others' disclosure of information about an individual could lead to actual privacy harm.…”
Section: Interpersonal Privacy Concerns On Osnsmentioning
confidence: 99%
See 1 more Smart Citation